ANALISIS KESADARAN PENGELOLAAN IJIN USAHA DAN PEMBUKUAN PADA UMKM YANG DIKELOLA DIFABEL DI KABUPATEN GUNUNGKIDUL - Siti Afidatul Khotijah; Agustina Prativi Nugraheni; Chaidir Iswanaji (KRISNA: Kumpulan Riset Akuntansi, 2022)
The awareness of business actors, especially those with disabilities, is not yet fully available. This study aims to analyze the awareness of people with disabilities who manage MSMEs in making an inventory of their products. In addition, the conformity of the product inventory method with the Statement of Financial Accounting Standards (PSAK) will also be analyzed. This study uses purposive sampling where the main requirement is individuals with disabilities who have MSME businesses in Gunungkidul Regency. This research is a descriptive qualitative study. The type of data used in this study is primary data derived from interviews and observations of respondents. The triangulation method will be used to test the validity of the data, while the data analysis uses coding analysis. The results of this study indicate that most of the people with disabilities in Gunungkidul who run MSMEs are physically disabled. MSMEs that are run by disability have not registered for a business license with the Gunungkidul Regency government. Bookkeeping has also not been fully applied to businesses managed by disability.